2015
DOI: 10.1080/14765284.2014.994845
|View full text |Cite
|
Sign up to set email alerts
|

What explains the performance of Chinese exporting firms?

Abstract: Drawing on the entry mode literature and the strategic tripod framework, we examine whether firm performance is influenced by its outward foreign direct investment (OFDI) mode, controlling other firm-, industry-and institution-specific factors. It is found that employing OFDI does not improve an exporting firm's performance. This is not surprising as anecdotal evidence shows that many Chinese firms with OFDI have been making loss in the host country. This may indicate exporting firms employ OFDI to seek comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 100 publications
(142 reference statements)
0
4
0
Order By: Relevance
“…For example, one of the firm-specific complementary resources considered by RBV is the international experience (Barney, Wright, and Ketchen 2001) that is built and accumulated from dealing with clients, competitors, and suppliers overseas (Camison and Villar-Lopez 2010). This knowledge is unique to a particular company and therefore cannot be easily acquired, assimilated, replicated, or applied (Zheng and Qu 2015). As such, it can support the development of new resources and capabilities difficult to obtain by competitors due to the high cost of developing, acquiring, or using that knowledge.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…For example, one of the firm-specific complementary resources considered by RBV is the international experience (Barney, Wright, and Ketchen 2001) that is built and accumulated from dealing with clients, competitors, and suppliers overseas (Camison and Villar-Lopez 2010). This knowledge is unique to a particular company and therefore cannot be easily acquired, assimilated, replicated, or applied (Zheng and Qu 2015). As such, it can support the development of new resources and capabilities difficult to obtain by competitors due to the high cost of developing, acquiring, or using that knowledge.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Exporting has been the first stage in their international expansion (Dunning 2003) as it has also been the most accessible, especially for small companies (it requires less fixed costs in comparison with other entry modes, etc (Zheng and Qu 2015)). Exporting has helped them to establish the necessary linkages abroad (Mathews 2006), to understand the market and develop capabilities to compete overseas (Gao 2008), and to build business relations with the aim of reducing the uncertainty and the asymmetry of information (Zheng and Qu 2015). Exporting has also supported learning along with economies of scale and scope which help in moving along the learning curve (Zheng and Qu 2015).…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…In his conceptual paper, Madhok (1997) argued that firms with specialized technology were more likely to prefer equity-based entry modes over contractual entry modes, unlike firms with more mature technology. Focusing on Chinese firms, Zheng and Qu (2015) found that technologybased capabilities and brands increased firm performance, irrespective of whether or not the firm conducted cross-border investments. Closely related to this study, Liang et al (2009) argued that prospectors and defenders possessed different types of capabilities resulting in opposite preferences with respect to shared versus full-ownership entry mode.…”
Section: Relevant Theory and Perspectivesmentioning
confidence: 99%